BIAS PEMBERITAAN SURAT KABAR ELEKTRONIK (SKE) (Studi Komparasi Isi berita tentang TKI di Arab Saudi pada detikcom dan sabq.org Periode 1 Maret sampai 30 Juni 2011) - , Muhammad Fahrudin Yusuf; , Dr. Ana Nadhya Abrar., M.E.S. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research focused on assessment bias of two most populer electronic newspaper (SKE) in Indonesia and Saudi Arabia, detikcom and sabq.org. They reported the issues of Indonesian Migrant Workers (TKI) In 2011. In this research, three ethical principles was used, i.e, truth, balance, and neutral. The principle of âtruthâ is measured by information depth, readability, chekability, and range/diversity on topic coverage. The principle of âbalanceâ is measured by source bias. The principle of neutral measured by personalization,emotionalism, dramatization, stereotype, juxtaposition, and linkage. Content analysis is used as method and codingsheet to collect data obtained from bias findings quantitatively vary in news about Indonesian Migrant Workers (TKI) reported detikcom and sabq.org in 2011. Statistically, bias difference was not found in the entire set categories, and in other categories bias is difference in significantly found.